Abdominal Pregnancy Implanted in the Spleen: A Case Report - Siddiqui, Md Nure Alom; Islam, Md Tohurul; Siddiqua, Fatema; Sultana, Shahnaj; Siddique, Abu Bakar (Anwer Khan Modern Medical College Journal, 2011)
Primary splenic pregnancy is the least common form of extrauterine pregnancy. We report a case of splenic pregnancy occurring in a 30-year-old woman presenting with acute abdomen and hemoperitoneum. Recognition of this rare form of gestation is of critical importance, owing to the risk of exsanguinations and death, and should be considered in the differential diagnosis of acute abdomen in women of reproductive age. We report a case of primary splenic pregnancy complicated by hemoperitoneum. Key Words : Ectopic Splenic Pregnancy; Acute Abdomen; Reproductive Age DOI: http://dx.doi.org/10.3329/akmmcj.v2i2.8171 AKMMC J 2011; 2(2): 36-38